Pemanfaatan Limbah Minyak Jelantah Sebagai Upaya Peningkatan Kepedulian Masyarakat Terhadap Lingkungan - Fitri Damayanti; Titin Supriyatin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Every household produces waste cooking oil that was discharged into the environment without any environmental control. This situation is exacerbated by the lack of public knowledge about the impact of it on health and the environment. Because of that, that was necessary to have an innovation in the use it into products of economic value as solid soap products. This activity was carried out with the PKK Karang Anyar partner, Sawah Besar, Central Jakarta which was conducted by online due to the Covid-19 Pandemic period. This activity was able to encourage the independence economic of partner eco-based. The partners agreed that the training provided could increase the added value of waste cooking oil waste, prevent environmental damage, and increase community entrepreneurship. In addition, it could reduce household expenditure in terms of reducing spending on washing agent related to the economy that was felt heavy when Pandemic Covid-19.